Manipulation of the taste of Regal Seedless (Vitis vinifera L.) table grapes - Fraser, W. J. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MscAgric (Viticulture and Oenology))--University of Stellenbosch, 2007.